Optic disc assessment in the emergency department: a comparative study between the PanOptic and direct ophthalmoscopes. Issue 12 (13th October 2011) - Petrushkin, Harry; Barsam, Allon; Mavrakakis, Milt; Parfitt, Andy; Jaye, Peter
Abstract : Optic disc assessment is an essential part of the neurological examination of acutely unwell patients. This study compares the PanOptic ophthalmoscope with the direct ophthalmoscope for accuracy of diagnosis and ease of use. Patient satisfaction was also compared for the two instruments. A single-masked prospective observational study was carried out. The authors showed that the PanOptic ophthalmoscope was more sensitive (p=0.03) and specific (p=0.03) than the direct ophthalmoscope. The PanOptic ophthalmoscope was preferred by both doctors (p=0.001) and patients (p=0.04) in terms of comfort and ease of use.